Ensaios em economia internacional e mercado de trabalho - Oliveira, Celina Santos de (2017)
The objective of this thesis is to investigate how access to international trade affects aspects of the Brazilian labor market, such as the movement between occupations and wages. Specifically, firstly, we seek to empirically investigate the determinants of upward occupational mobility for Brazil in a period between 2003 and 2013, highlighting the effect of the export sector on this mobility. To meet this goal we used Logit and Ordered Logit on the RAIS and SECEX data set. In addition, in order to minimize the bias of sample selection on the matching of the workers with the exporting firms, the method of Balanced Propensity Scores by Entropy was applied. As a result, it was found that the white workers with higher level of education and a positive wage differential between occupations, increases the probability of a worker changing occupation to a higher level, whileolder,manworkerandbeinginaregionwithhighlyeducatedforeignmigrantsreduce this probability. Alongside this, the positive effect of the export environment is highlighted when mobility is accompanied by a change of employer and by reductions in the costs of such mobility when in the presence of the export sector. This is especially true if this worker from this sector is attracted by a non-exporting company. In a second moment, it is intended to answer if there are differences in the realization of matching of workers between Brazilian exporting and non-exporting companies. The same data provided by RAIS was also used for a period after the commercial opening between 2003 and 2013. It was based on the theoretical model of Bombardini, Orefice e Tito (2015) which considers the realization of matching in an environment with workers and heterogeneous firms with search frictions in the labor market. A variable of types of workers was constructed using three methodologies. The first one used the theoretical model approach that reduced to the use of the wage variable as proxy for types of workers and the second and third one uses a traditional wage regression that was estimated following Guimarães e Portugal (2010) and Zou (2006) with Adaptive Lasso. Next, the measures of average and dispersion of the type of workers at the firm level were constructed and, on these, the effect of these firms in the export sector was investigated. As a result, it was found that exporting firms select a higher average of types of workers, while these types are less dispersed in relation to that average. Thus, exporters pay higher wages because, among other factors, they employ the best workers.